Fuzzy Mode Enhancement and Detection for Color Image Segmentation - Ludovic Macaire; Claudine Botte-Lecocq; Olivier Losson (EURASIP Journal on Image and Video Processing, 2008)
This work lies within the scope of color image segmentation by pixel classification. The classes of pixels are constructed by detecting the modes of the spatial-color compactness function, which characterizes the image by taking into account both the distribution of colors in the color space and their spatial location in the image plane. A fuzzy transformation of this function is performed, based on fuzzy morphological operators specifically designed for mode detection. Experimental segmentation results, using several synthetic and benchmark images, show the interest of the proposed method.